Tra “complesso del tiranno” ed “ossessione della stabilità”: il disegno delle istituzioni democratiche dopo la caduta del fascismo e del franchismo - Lanza, Orazio (SocietàMutamentoPolitica, 2015)
Democracies are often the outcome of popular mobilizations, but, almost always, only a given group leads the process of democratization. In particular, the formal design of democratic institutions is, necessarily, the product of the political efforts of an élite, whose beliefs and preferences are particularly relevant. This essay aims to identify which legacies of the past have affected the institutional design of democratic regimes established in Italy and Spain after the fall of Fascism and Francoism. In particular it is highlighted the crucial role played by historical legacies, authoritarian legacies, historical memory and political learning. The differences in timing, mode of transition, in composition of the elite and some other factors affect the weight of the legacy of the past. The comparison between Italy and Spain provide a more useful information and explanation for the differences in institutional designs of two countries.